Preservação de córnea humana nos meios eusol-c® e optisol-gs® - Leonardo Rodrigues Pereira (2011)
More than a decade has already passed since the means of preservation, medium term, of corneas was introduced in Brazil. Two methods have been used in the preservation of corneas in Brazil: Optisol-GS® (Bausch e Lomb, USA.) and Eusol-C® (Al.Chi.Mia, Italy). Both are indicated for preservation of the endothelial function of the cornea for 14 days. This is the most widespread method of preservation of corneas for transplants. Up to the present there has not appeared, in the literature, a comparative clinical study between these two methods, and this work aims to fill this gap. In this study, 61 transplanted corneas were evaluated, with average endothelial cellular density of 1085 ± 554.1 cells/mm2, and average follow-up of 25.8 ± 15.9 months. These corneas were divided for preservation into two groups: Eusol-C® with n = 31, average post operative follow-up time 26.8 ±7.4 months and average count of endothelial cellular density of 949.8 ± 354.7 cells/mm2, and Optisol-GS® with n = 30, average postoperative follow-up time 24.8 ± 20.1 months for penetrating keratoplasty surgery and average of 1.225.2 ± 682.1 cells/mm2 of endothelial cellular density. In this study, we confirmed the efficacy of both the Eusol-C® and the Optisol-GS® in the preservation of the human cornea for transplants, without detecting any statistically significant difference for the two methods as regards biomicroscopy, endothelial cellular density, topography, pachymetry and visual acuity. The preservation of the corneas by these methods does not influence the quality of life of the patients undergoing transplant in the long term follow-up